Inclusion complexes of imidazolium carboxylate-metal species in the water-soluble sulfonated calix[4]arene system. Issue 1 (17th December 2020) - Ling, Irene; Sobolev, Alexandre N.; Dalgarno, Scott J.
Abstract: Two multi-component crystal structures comprising a carboxylic acid-functionalized imidazolium zwitterion, a p -sulfonatocalix[4]arene anion and aquated metal ion (Na + or Y 3+ ) with or without an auxiliary component (the 3-methoxyphenyl-triphenylphosphonium cation) are reported. The carboxylic acid-functionalized imidazolium ion binds either as a monodentate or a bidentate ligand depending on the nature of the metal ions, and a bi-layer arrangement prevails in the extended structure regardless of the type of metal ion employed or presence/lack of auxiliary component. Graphical Abstract: